2018
DOI: 10.1002/pen.24990
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic reinforcement of epoxy/basalt fiber composites with dimensionally different nanoparticles

Abstract: Epoxy/basalt fiber composites were modified by 2D montmorillonite (MMT), 0D nanoSiO2, or 2D MMT/ 0D nanoSiO2 double nanoparticles. Mechanical tests showed that all the modified composites had considerably improved interlaminar shear strength and notch impact strength compared with the unmodified epoxy/basalt fiber composites, and that the double nanoparticle‐modified composites displayed the greatest improvement. X‐ray diffraction, transmission electron microscopy, and scanning electron microscopy revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
2
6
0
Order By: Relevance
“…The σ max results at 25 • C are in line with literature reports for materials strengthened with chopped fibre and powder fillers [16][17][18][19][20]. In theoretical considerations described in the literature, the worst strength properties have been seen for composites containing chopped or ground fibre and fibre mats providing the reinforced plastics with both spatial and in-plane isotropy [21][22][23][24][25].…”
Section: Static Bending Strengthsupporting
confidence: 87%
“…The σ max results at 25 • C are in line with literature reports for materials strengthened with chopped fibre and powder fillers [16][17][18][19][20]. In theoretical considerations described in the literature, the worst strength properties have been seen for composites containing chopped or ground fibre and fibre mats providing the reinforced plastics with both spatial and in-plane isotropy [21][22][23][24][25].…”
Section: Static Bending Strengthsupporting
confidence: 87%
“…Nanoparticles can also produce an anchor effect between fibers and resin, which can effectively increase the bonding forces between the fibers and the matrix, resulting in composites with superior mechanical properties. For example, Li et al [66] found that the impact strength and interlaminar shear strength of BF composites with added nano-SiO 2 increased by 139.73% and 27.25%, respectively.…”
Section: Bf Coated With Nanoparticlesmentioning
confidence: 99%
“…Compared with GO, the SGO filler material is more efficient. Li et al [ 13 ] examined the epoxy/basalt fiber laminates with the incorporation of 2D montmorillonite (MMT), 0D nanoSiO 2 and combined 2D MMT/0D nanoSiO 2 attained efficiently increased in ILSS and notch impact strength compared with plain epoxy/basalt fiber composites, the highest improvement in the incorporated composite of 2D MMT/0D nanoSiO 2 proved experimentally and had unique microstructure phase by scanning electron microscope (SEM) results. The mechanical behavior of aluminum and basalt fiber epoxy FMLs composite in addition with modified NC of 1, 3, and 5 wt% experimental results showed that the Charpy impact absorbed the highest energy in 3 wt% NC content and decreased in ILSS due to the cluster of NC particles studied by Bahari‐Sambran et al [ 14 ] Sampath and Santhanam [ 15 ] evaluated the effect of moringa and bagasse ash filler particles added in epoxy/basalt composites exhibits better mechanical properties, corrosion resistance, and water absorption resulting in moringa/basalt‐epoxy composites.…”
Section: Introductionmentioning
confidence: 99%